Inclusive growth : the global challenges of social inequality and financial inclusion - Thomas, Howard; Hedrick-Wong, Yuwa (Bingley, U.K. : Emerald Publishing Limited, 2019)
Inclusive growth ensures the benefits of a growing economy extend to all segments of society. Unleashing people's economic potential starts with connecting them to the vital networks that power the modern economy. Implementing inclusive growth is a means of democratizing productivity and it is essential to reduce the widening gap between the wealthy and the poor in both developed and developing economies. This book arose out of a research partnership between the Mastercard Center for Inclusive Growth and Singapore Management University (SMU). It demonstrates the logic of inclusive growth, explaining its principles and the enabling models that define it. It also examines the means to creatively address financial and social inclusion and thus improve social equality. The focus is to provide basic rights for all in society to access and participate in the vital networks of services and know-how that are the indispensable enablers of increasing productivity in modern economic production. Business, government, and civil society must devise implement effective initiatives so that inclusive growth is achieved through the global democratization of productivity.Inclusive Growth: The Global Challenges of Social Inequality and Financial Inclusion will appeal to researchers and faculty in management and business schools, leaders with a moral and ethical sense of social responsibility, as well as academics interested in economics, economic policy, and economic development.
Prelims -- Enabling models of inclusive growth from financial inclusion to democratizing productivity -- What is "financial inclusion"? -- How digital finance and Fintech can improve financial inclusion -- What is social inclusion and how financial and social inclusion are inextricably linked -- Pathways to inclusive growth: social capital and the bottom of the pyramid -- The role of social enterprises and entrepreneurship in driving inclusive growth -- The role of women entrepreneurs in inclusive growth -- Postscript: Reflections and future directions -- Appendix 1 -- Appendix 2 -- Appendix 3 -- Index.
Includes index.
Print version record
Keywords: Equality; Social integration; Entrepreneurship; Business & Economics -- Economics -- General; Economics